Legal Framework for the Management of External Public Debt in Zimbabwe - Mapuvire, Victor; Mapuvire, Davidzo (International Journal of Law and Public Policy (IJLAPP), 2022)
The establishment of an effective governance structure consisting of a sound institution and legislative framework is one of the fundamental requirements for having a prudent and effective debt management system capable of ensuring debt sustainability in place. There are numerous legal arrangements that have been established by the GoZ for the management of the country’s external public debt. This paper therefore examines the legal arrangements put in place for the management of external public debt in Zimbabwe. Methodologically, the paper was based on a qualitative approach and relied on secondary data obtained from original or primary sources. Findings from the paper reveal that, the legal framework for debt management in Zimbabwe comprises of; the Constitution of Zimbabwe Amendment (No. 20) Act 2013, the Public Finance Management Act [Chapter 22:19] of 2009, the Public Debt Management Act [Chapter 22:21] of 2015 as well as the Reserve Bank of Zimbabwe Act [Chapter 22:15] of 2010. However, even though such a legal framework somewhat meets the minimum acceptable standards for the management of external public debt, it can be noted that there have some areas of concern with the current legislation framework that required attention. Such a scenario therefore undermines the effective management of the country’s external public debt. This paper thus recommends that there is need to reform the legal framework for the management of external public debt in Zimbabwe.